Multivariate analysis of the adoption of cacao productive technologies: Evidence from a case study in Colombia - José María Martínez; Eliana Martínez Pachón (Economía Agraria y Recursos Naturales)
Multivariate and ordered Probit models were used to study the determinants of the adoption and extent of adoption of agronomic practices among cacao farmers in Nariño, Colombia, with data from 353 farmers in the mountain region. Results suggest that farmers’ adoption decisions are made on a joint basis, further validating the use of a multivariate approach. The presence of illegal crops creates strong disincentives that affect the possibility of more significant technological improvements. Adequate access to agricultural technical assistance strongly increases rates of adoption. Evidence suggests that efforts are necessary to better target resource-poor farmers.